How sex changed : a history of transsexuality in the United States - Meyerowitz, Joanne J. (Joanne Jay) (Harvard University Press, 2002)
"How Sex Changed is a fascinating social, cultural, and medical history of transsexuality in the United States. Joanne Meyerowitz tells a powerful human story about people who had a deep and unshakable desire to transform their bodily sex. In the last century when many challenged the social categories and hierarchies of race, class, and gender, transsexuals questioned biological sex itself, the category that seemed most fundamental and fixed of all. From early twentieth-century sex experiments in Europe, to the saga of Christine Jorgensen, whose sex-change surgery made headlines in 1952, to today's growing transgender movement, Meyerowitz gives us the first serious history of transsexuality. She focuses on the stories of transsexual men and women themselves, as well as a large supporting cast of doctors, scientists, journalists, lawyers, judges, feminists, and gay liberationists, as they debated the big questions of medical ethics, nature versus nurture, self and society, and the scope of human rights."--